On Assessing Public Leadership as Basis for Public Service Enhancement - Basilan, Romel (JPAIR Multidisciplinary Research, 2020)
The descriptive quantitative research explored the different dimensions of public leadership in relation to organizational productivity to analyze the service rendered by the Provincial Government of Batangas, Philippines. This focused on the assessment of innovation in terms of inputs, processes, and outcomes with respect to the demographic profile of the locale. With this assessment of innovation, the paper withheld that innovation is significantly affected, and the results vary in terms of age, sex, educational attainment, and years in service of the government employees. Expressively, dimensions of public leadership bestowed relationship to give innovative public service. It also deliberately manifested that in consideration of the profiling of the employees, the government can maximize the human resources to optimal innovation, creativity, and skills, which leads to employees’ effectiveness, creative ideation, and implementation of best practices. This paper strongly agreed that productivity in the workplace is inevitable. In the end, this paper would propose an enhancement program that might help to hoist productivity and innovation among Batangas employees and administrative personnel.